Optimization and performance studies of NFDK membrane for ionic separation from aqueous solutions - Qadir, D. (Springer Science and Business Media Deutschland GmbH, 2022)
The modern world is facing one of the serious threats (i.e., freshwater) to the life on the planet and efforts are being made to provide freshwater for the current population. The novelty of this work lies in a comprehensive evaluation of properties and performance of commercially available NFDK membrane for various monovalent (NaCl) and divalent (CaCl2, MgCl2) salts, particularly tin salt (SnCl2). The central composite design (CCD) and response surface methodology were applied in designing the experiments to assess the effects of the numerical factors, i.e., pressure, concentration, and categorical factors like salt type, on the flux and rejection. The characterization results showed the asymmetric structure with three distinct layers, and hydrophilic surfaces with negative surface charges and thus was expected to perform well depending upon other operational parameters. It was deduced that the Donnan exclusion mechanism dominantly regulated theÂ tin ion rejection 95.14 and permeate flux 71.18Â L/m2.h at 10Â bar pressure. The optimization results showed that predicted resultsÂ were in good agreement with experimental results. TheÂ RÂ 2= 0.99 showed the effectiveness of CCD in the optimization of NFDK performance. Â© 2021, Institute of Chemistry, Slovak Academy of Sciences.